2009
DOI: 10.1152/japplphysiol.90865.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hypophagia induced by glucocorticoid deficiency is associated with an increased activation of satiety-related responses

Abstract: Uchoa ET, Sabino HA, Ruginsk SG, Antunes-Rodrigues J, Elias LL. Hypophagia induced by glucocorticoid deficiency is associated with an increased activation of satiety-related responses. J Appl Physiol 106: 596 -604, 2009. First published November 20, 2008 doi:10.1152/japplphysiol.90865.2008.-Glucocorticoids have major effects on food intake, demonstrated by the decrease of food intake following adrenalectomy. Satiety signals are relayed to the nucleus of the solitary tract (NTS), which has reciprocal projectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 54 publications
1
26
0
1
Order By: Relevance
“…A2 neurons seem to be activated in every experimental situation in which food intake is inhibited, including normal satiety [359][360][361][362][363][364]. A2 neurons are recruited in a graded manner in rats after eating, such that larger meals activate larger numbers of A2 neurons [365].…”
Section: Noradrenergic Neuronsmentioning
confidence: 99%
“…A2 neurons seem to be activated in every experimental situation in which food intake is inhibited, including normal satiety [359][360][361][362][363][364]. A2 neurons are recruited in a graded manner in rats after eating, such that larger meals activate larger numbers of A2 neurons [365].…”
Section: Noradrenergic Neuronsmentioning
confidence: 99%
“…The food intake and body weight gain are reduced in ADX animals, being these effects reversed by glucocorticoid replacement (Freedman et al, 1985;Uchoa et al, 2009aUchoa et al, , 2009bUchoa et al, , 2010. Furthermore, ADX is effective in diminishing hyperphagia and obesity under diverse experimental conditions (Bruce et al, 1982;Dubuc and Wilden, 1986;Yukimura et al, 1978).…”
Section: Neuropeptidesmentioning
confidence: 99%
“…Recent studies have demonstrated that the hypophagic response induced by ADX is associated with increased activation of satiety-related responses mediated by brainstem and hypothalamic circuits (Uchoa et al, 2009a(Uchoa et al, , 2009b. Accordingly, the activation of NTS neurons, assessed by the increased number of cells expressing the nuclear c-Fos protein, is increased in ADX animals after feeding, indicating that this nucleus may be involved in the increased satiety responses following glucocorticoid deficiency (Uchoa et al, 2009a). Interestingly, the activation of CRF and OT neurons was also enhanced in the PVN of fed ADX rats, indicating that, besides the brainstem, the hypothalamus may be also involved in these satiety-related responses.…”
Section: Neuropeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral adrenalectomy (ADX) induces hypophagia [1][2][3] and is a well-established experimental model to investigate the mechanisms underlying the hypophagic effect observed in the primary adrenal insufficiency in humans [4]. Accordingly, glucocorticoid replacement to adrenalectomized (ADX) animals reverses the reduction of food intake [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%